1997
DOI: 10.1016/s0741-5214(97)70211-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-P-selectin antibody decreases inflammation and thrombus formation in venous thrombosis

Abstract: Anti-P-selectin antibody decreases vein wall inflammation and thrombus formation. Inhibition of P-selectin may be useful in venous thrombosis prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
89
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 22 publications
6
89
0
1
Order By: Relevance
“…Moreover, elevated levels of sP-sel might be involved in the recurrent thrombotic process of angina (45) and in restenosis (46). Our findings support and provide an explanation for the promising results of antithrombotic therapies directed against P-selectin in various thrombotic models such as stroke (47), or deep vein thrombosis (48). A reduction in numbers of circu- TF-induced Xa activity was determined on the corresponding fraction of microparticles.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, elevated levels of sP-sel might be involved in the recurrent thrombotic process of angina (45) and in restenosis (46). Our findings support and provide an explanation for the promising results of antithrombotic therapies directed against P-selectin in various thrombotic models such as stroke (47), or deep vein thrombosis (48). A reduction in numbers of circu- TF-induced Xa activity was determined on the corresponding fraction of microparticles.…”
Section: Discussionsupporting
confidence: 73%
“…Platelets play critical roles in both hemostasis and inflammation. Studies have shown that platelet surface glycoprotein (GP) Ib-VI 31 and p-selectin 32 or ADP, 33 released from activated platelets, may provide receptors or signal for recruiting neutrophils and monocytes. The accumulation and activation/degranulation of neutrophils may result in the massive release of granular contents, including neutrophil extracellular traps (NETs) 20 and HNP1-3 34 at the sites of vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…One consequence is the inhibition of the interaction between P-selectin and its receptor, which occurs on different cell types, including platelets and leukocytes. Inhibiting the interaction between P-selectin and PSGL-1 with P-selectin antagonists (recombinant soluble PSGL-immunoglobulin), intravenously administered soluble ligands, or an orally administered nonprotein inhibitor (PSI-697) markedly attenuated the prothrombotic effect in a mouse model (13)(14)(15)(16)(17). Statin medication has recently been reported to reduce sP-selectin concentrations significantly (38 -40 ), and sP-selectin concentration was inversely correlated with the progression of coronary heart disease (38 ).…”
Section: /97mentioning
confidence: 99%